High magnetostriction parameters of sintered and magnetic field annealed Ga-substituted CoFe2O4 - Anantharamaiah, P. N.; Joy, P. A. (Materials Letters, 2017)
Impact of substitution of the non-magnetic ion Ga3+ for Fe3+ on the magnetostriction parameters of CoFe2O4 has been investigated for samples prepared by a tartrate-gel method. All the Ga-substituted compositions in CoGaxFe2-xO4 (0 <= x <= 0.3) showed higher strain sensitivity (d lambda/dH), at low magnetic fields, compared to that of the unsubstituted sample. The magnetostriction strain (lambda) and d lambda/dH of the composition CoGa0.1Fe1.9O4 could be enhanced from -228 to -296 ppm and -2.20 x 10(-9) to -3.55 x 10(-9) miA, respectively, at low magnetic fields, after magnetic field annealing at 300 degrees C. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: Cobalt ferrite; Magnetic field annealing; Magnetic materials; Magnetostriction; Substitution